Suppression of Berberine and Probiotics (in vitro and in vivo) on the Growth of Colon Cancer With Modulation of Gut Microbiota and Butyrate Production - Huang, Chao; Sun, Ying; Liao, Sheng-rong; Chen, Zhao-xin; Lin, Han-feng; Shen, Wei-zeng (Frontiers in Microbiology, 2022)
Objective This study aimed to explore the inhibitory effect of berberine and probiotics on the growth of colon cancer cells in vitro and in vivo, and the regulatory influence on the gut microbiome and butyrate production. Methods Colon cancer cell HT29 was used to establish a xenograft model of nude mice and an in vitro model. 44 nude mice and HT29 cells were divided into control, model, model+berberine, model+probiotics, model+combination of berberine with probiotics (CBP). Live combined Bifidobacterium, Lactobacillus and Enterococcus powder (LCBLEP) was used as a probiotics preparation. LCBLEP was cultured in the liquid medium under anaerobic conditions (the number of viable bacteria should reach 1×108CFU), then the supernatant was collected and called it probiotic supernatant (PS). Model+berberine and model+probiotics group were treated with berberine and LCBLEP or PS for 4 weeks in vivo or 48h, 72h, 96h in vitro, respectively. Tumor volume or cell proliferation were measured. Gut microbiota was pyrosequenced using 16S rDNA amplicon. HDAC1 mRNA level in HT29 cells and sodium butyrate (SB) expression in serum of mice were detected by QPCR and ELISA. Results The inhibitory effect of LCBLEP on the tumor growth was more significant, especially at 11d-21d (P<0.05). Inhibition of BBR on in vitro proliferation was concentration-dependent. The suppression of 75% PS (probiotics supernatant) on the proliferation was the most significant. Berberine dramatically increased the abundance of Bacteroidetes and Proteobacteria, with reduced Ruminococcus, followed by the LCBLEP. Berberine and LCBLEP or CBP improved the Alpha and beta diversity, and significantly affected the biomarker and metabolic function of the gut microbe in nude mice with colon cancer. Level of HDAC1 mRNA was reduced in the the HT29 cells treated with BBR or PS (P<0.05), and the mice treated with BBR revealed significantly increased concentration of SB in serum (P<0.05), and the inhibitory effect of SB on proliferation of HT29 cells was stronger than panobinostat and TSA. Conclusion Berberine can be used as a regulator of intestinal microbiome similar to the probiotics through mediating the SB production during reducing the growth of colon cancer.